The synthesis of sulfur-doped graphite nanostructures by direct electrochemical conversion of CO2 in CaCl2NaClCaOLi2SO4. (April 2019) - Hu, Liwen; Yang, Zhikun; Yang, Wanlin; Hu, Meilong; Jiao, Shuqiang
Abstract: The electrochemical synthesis of sulfur-doped nanostructured graphite including graphene and carbon nano-tube via direct electrochemical conversion of CO2 in CaCl2 NaClCaOLi2 SO4 has been realized at a relative low temperature (675 °C). The results indicate that sulfur can successfully incorporate into carbon matrix and the graphitization degree can also be enhanced by introducing sulfur. In addition to SO4 2−, Li + will also have positive effect on improving the graphitization of carbon deposition. Aggregated carbon particles are included in all samples while ultrathin graphite sheet, wire-like carbon, carbon nano-tube and interwoven carbon chains can be obtained in some cases at different electrolytic conditions. This work opens up a novel way to fabricate heteroatom-doped nanostructured carbons from carbon dioxide. Graphical abstract: Image 1